Certain Biochemical Changes in Haemolymph of Eri Silkworm, Samia Cynthia Ricini after Inoculation with Bacteria - Gundeti, Ravindar; Swetha sudha, N.; Rajalingam, Geeta; Nagaraja Rao, P. (International Journal of Applied Sciences and Biotechnology, 2015)
The insect immune system exists to protect the host from pathogenic invaders and from other harmful insults. Upon bacterial infection insect haemolymph may lead to fatal consequences and it plays a most important role in transport and storage of nutrients, amino acids and free amino acids concentrations are marked changes for substrates by the immune system, these substrates are provide energy and precursors for the synthesis of new cells, effecter molecules, and protective molecule. We have been studied the certain biochemical changes in bacterial challenged Eri silkworm haemolymph at various time intervals. Results shows that the proteins and amino acids levels were significantly elevated and 18 individual free amino acids were found and that are quantitatively variation in the haemolymph after challenge with gram –ve and gram +ve bacteria when compared and control and sterile haemolymph. We may conclude that these were directly involved in the antimicrobial immune response of Eri silkworm innate immunity Int J Appl Sci Biotechnol, Vol 3(2): 236-242 DOI: http://dx.doi.org/10.3126/ijasbt.v3i2.12453